Explicit and Implicit Timing of Short Time Intervals: Using the Same Method. (January 2020) - Soltanlou, Mojtaba; Nazari, Mohammad Ali; Vahidi, Parisa; Nemati, Parvin
Up until now, there has been no study conducted in the field of time perception using very short intervals for a direct comparison between implicit and explicit timing tasks in order to uncover plausibly different underlying mechanisms. Therefore, the aim of this study was to compare human time estimation during implicit and explicit timing tasks with short intervals and the same method. A total of 81 adults were divided into three groups and completed two tasks with one of three different intervals: 500, 1, 000, and 2, 000 ms. The results revealed an overestimation for all three intervals of the implicit timing task, while participants overestimated 500 ms but underestimated 1, 000 and 2, 000 ms intervals of the explicit timing task. Moreover, explicit time estimation was more precise than implicit time estimation. We observed the opposite pattern as compared to a few previous studies with long intervals: Short intervals were perceived longer in the implicit timing task as compared to the explicit timing task. We concluded that nontemporal contents represent passing time during the implicit timing task but unlike temporal dimension during the explicit timing task. Therefore, even the same method of measurement led to a different performance in implicit and explicit timing tasks.